Superheavy Dark Matter in the Supersymmetric Economical 3-3-1 Model - Huong, Do Thi (Communications in Physics, 2015)
We suggest the supersymmetric particles contained in the supersymmetric economical 3-3-1model were produced during the heating time. They have not been thermodynamic equilibrium when it frozeout. It leads to the lightest supersymmetric particle can be a good candidate for superheavy dark matter.With assumption the lightest supersymmetric particle is Bino, we show that the correct contribution of thesuperheavy dark matter species to the present critical density requires the Bino mass is order 1012 GeVand there is not exists a large mass hierarchy of the superpartner in the considered model.